Exchange Rate Volatility: Effect on Foreign Direct Investment ‎Inflows in Nigeria - Njoku, Charles Odinakachi; Ugwu , Kelechi Enyinna; Nwaimo , Chilaka Emmanuel; Nwadike, Emmanuel Chijioke; Eke , Chinonso Karen; Ikeogu , Christopher Chiedozie; Omeire , Edward Uche; Otuonye , Anthony ‎Ifeanyi; Echeme , Ibeawuchi Ifeanyi; Eriwa , Babatunde Oyelade (International Journal of Accounting and Economics Studies, 2025)
A nation’s high GDP, high exports, and influx of foreign direct investment all indicate its economic ‎growth and stability; yet, exchange rate risk—that is, the possibility of a country’s currency ‎depreciating or appreciating—can also cause concern for international investors and the nation of ‎origin. The uncertainty surrounding their currency exchange rate presents a formidable challenge: ‎is it better for their economy to have low or high volatility, and does it have the potential to draw ‎in or hinder FDI? The research used the Autoregressive Distributed Lag (ARDL) model to ‎investigate the effect of exchange rate volatility on foreign direct investment inflows into Nigeria ‎from 1986 to 2023. The study aims to determine whether the Nigerian government should ‎impose more stringent measures on foreign direct investment flows while formulating strategies to ‎ensure stable exchange rates. The ARDL bounds testing approach was utilized in the cointegration ‎analysis to investigate the relationship between the variables in the model. The result of the ‎analysis revealed that inflation and interest rates have a long-term negative effect on foreign direct ‎investment inflows to Nigeria as a result of high currency volatility. Also, exchange rate ‎fluctuations have a long-term, significant negative effect on foreign direct investment inflows into ‎Nigeria, highlighting the concerns of international investors regarding currency instability in the ‎country. The research recommends that Nigeria diversifies its economy in order to attract more ‎Foreign Direct Investment‎.